Analisis Kebutuhan Keterampilan Agribisnis di Era Digital Studi Kasus Di Sekolah Vokasional Pertanian - Eni Nopia; Alif Ilham Akbar Fatriansyah; Muhammad Sarifudin; Aan Budianto (CV. Creative Tugu Pena, 2021)
An analysis of agribusiness skills needs in the digital era shows that farmers and agribusinesses need to master digital skills to improve efficiency, productivity, and competitiveness. These skills include the use of information and communication technology (ICT), data analysis, and digital marketing. Digital transformation has had a significant impact on the agricultural sector in Indonesia by improving operational efficiency, opening new market opportunities, and introducing the concepts of digital agriculture and agriculture 4.0. Although the government has encouraged agricultural digitalization through policies and programs, farmers still face challenges such as limited land, climate change, and limited market access. Collaboration between the government, the private sector, and non-profit organizations is needed to support farmers' adoption of digital technology to improve their efficiency, productivity, and well-being. Challenges such as lack of internet access, low digital literacy, and high technology implementation costs also need to be addressed through cross-sectoral collaboration. This study highlights the critical need for agribusiness skills in the digital era, particularly in the case study of agricultural vocational schools, which represent a significant opportunity in the digital era, with the aim of overcoming obstacles to the digital transformation of the Indonesian agricultural sector.